Depletion of mitochondrial acyl carrier protein in bloodstream-form Trypanosoma brucei causes a kinetoplast segregation defect. - Clayton, A; Guler, J; Povelones, M; Gluenz, E; Gull, K; Smith, T; Jensen, R; Englund, P (2011)
Like other eukaryotes, trypanosomes have an essential type II fatty acid synthase in their mitochondrion. We have investigated the function of this synthase in bloodstream-form parasites by studying the effect of a conditional knockout of acyl carrier protein (ACP), a key player in this fatty acid synthase pathway. We found that ACP depletion not only caused small changes in cellular phospholipids but also, surprisingly, caused changes in the kinetoplast. This structure, which contains the mitochondrial genome in the form of a giant network of several thousand interlocked DNA rings (kinetoplast DNA [kDNA]), became larger in some cells and smaller or absent in others. We observed the same pattern in isolated networks viewed by either fluorescence or electron microscopy. We found that the changes in kDNA size were not due to the disruption of replication but, instead, to a defect in segregation. kDNA segregation is mediated by the tripartite attachment complex (TAC), and we hypothesize that one of the TAC components, a differentiated region of the mitochondrial double membrane, has an altered phospholipid composition when ACP is depleted. We further speculate that this compositional change affects TAC function, and thus kDNA segregation.